Correlating preoperative imaging with intraoperative fluoroscopy in iliosacral screw placement - Eastman, Jonathan G. (J Orthop Traumatol, 2015)
BACKGROUND: Percutaneous iliosacral screw placement can successfully stabilize unstable posterior pelvic ring injuries. Intraoperative fluoroscopic imaging is a vital component needed in safely placing iliosacral screws. Obtaining and appropriately interpreting fluoroscopic views can be challenging in certain clinical scenarios. We report on a series of patients to demonstrate how preoperative computed tomography (CT) imaging can be used to anticipate the appropriate intraoperative inlet and outlet fluoroscopic views. MATERIALS AND METHODS: 24 patients were retrospectively identified with unstable pelvic ring injuries requiring operative fixation using percutaneous iliosacral screws. Utilizing the sagittal reconstructions of the preoperative CT scans, anticipated inlet and outlet angle measurements were calculated. The operative reports were reviewed to determine the angles used intraoperatively. Postoperative CT scans were reviewed for repeat measurements and to determine the location and safety of each screw. RESULTS: Preoperative CT scans showed an average inlet of 20.5° (7°–37°) and an average outlet of 42.8° (30°–59°). Intraoperative views showed an average inlet of 24.9° (12°–38°) and an average outlet of 42.4° (29°–52°). Postoperative CT scans showed an average inlet of 19.4° (8°–31°) and an average outlet of 43.2° (31°–56°). The average difference from preoperative to intraoperative was 4.4° (−21° to 5°) for the inlet and 0.45° (−9° to 7°) for the outlet. The average difference between the preoperative and postoperative CT was 2.04° (0°–6°) for the inlet and 2.54° (0°–7°) for the outlet. CONCLUSION: There is significant anatomic variation of the posterior pelvic ring. The preoperative CT sagittal reconstruction images allow for appropriate preoperative planning for anticipated intraoperative fluoroscopic inlet and outlet views within 5°. Having knowledge of the desired intraoperative views preoperatively prepares the surgeon, aids in efficiently obtaining correct intraoperative views, and ultimately assists in safe iliosacral screw placement. LEVEL OF EVIDENCE: IV, Retrospective case series.